Study of Qualitative Nature and Structure of the Local Chicken Population in Southeast Sulawesi - Muhammad Amrullah Pagala; Natsir Sandiah; Achmad Selamet Aku; Rusli Badaruddin; La Ode Muh Munadi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Kampong chicken, also known as a local chicken, is a native Indonesian chicken that has adapted, lived, developed, and reproduced for a long time, both in certain habitat areas and in several places. The study aimed to determine local chickens' qualitative nature and population structure in Southeast Sulawesi with six months in Kolaka Regency, Konawe Regency, and Buton Regency. Determination of the research population is based on the most significant, medium, and low population of chickens in each district. The research sample, which is 300 people, uses the purposive sampling method with data collection methods in interviews observation documentation. The results showed that native chickens in Southeast Sulawesi had colored and colorless plumage, wild and Columbian black feather patterns, plain striated feather patterns, and flickering gold and silver feathers, while the shank colors were white/yellow and black/gray, and the shape of a comb. Peas, single, and rose.